TINJAUAN PENGARUH BUDAYA ORGANISASI TERHADAP KOMITMEN KARYAWAN: STUDI LITERATUR TERBARU - Fani Oktaviani Agustin; Indah Rosdiyan, Mita Widyaningrum, Netty Merdiaty (ADISAM PUBLISHER, 2024)
Organizational culture is a crucial factor that shapes workplace values, norms, and behaviors, which can influence employee engagement and loyalty to the organization. A strong organizational culture that is in line with employees' values can increase employees' emotional, normative, and continuance commitment. This research was conducted by means of a literature review. The research confirms that organizational culture as one of the main factors in employee commitment